If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3h + -2) = 14 Reorder the terms: 2(-2 + 3h) = 14 (-2 * 2 + 3h * 2) = 14 (-4 + 6h) = 14 Solving -4 + 6h = 14 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 6h = 14 + 4 Combine like terms: -4 + 4 = 0 0 + 6h = 14 + 4 6h = 14 + 4 Combine like terms: 14 + 4 = 18 6h = 18 Divide each side by '6'. h = 3 Simplifying h = 3
| 2x-8x=-5 | | 2(x-3)=2x+4 | | -(w+5)=14 | | 9a^3+15a^2-36a=0 | | -3(5s-4)-12=2(9s+7)-2 | | 42x^2-15x-3=0 | | -2(-3x-w)-(2w-6x)= | | 5x^2+6x=12x-9 | | 8(x+2)=8x+16 | | 0.25x+.05(2-x)=.10(37) | | -5(x-4)=40 | | 8(x+6)-3(2x-7)=127 | | 1=d/10-12 | | 24v^2-9v+32v-12=0 | | 5y=-2.8 | | 7n-1=9+10n-12 | | 3x^2+2x-5=2x^2-2 | | 0.5=-8 | | 0.36(6)+0.04x=0.12(18+x) | | 4(6a-16)+2(2a+12)=4 | | 0.41x=8.2 | | -3(3y+v)+6(4v-4y)= | | 24-4(7-2t)=4(t-1) | | 950=25h+40 | | 1/2=-8 | | c=25h+40 | | -(2x+5)-9x= | | -x-2y=8 | | 3*32*3+u=(3*3*3-3*8)(2)+u | | 8(3x-6)=2(12x+4) | | -(4u-6)-u= | | 8x-3(3x+2)= |